Central de serviços compartilhados: métricas e resultados de implantação - Santos, Márcia da Silva (2009)
The attention given to the central attractions of the implementation of shared services, also known as shared services, gain significant space in strategic planning of organizations, especially those that have several business units. This dissertation aims to describe the main results of the implementation of a shared services central through the use of certain metrics in the strategic plan of the corporation and also to identify the key tools that assist and strengthen the use of metrics as part of the company's strategic planning. Identify the course of implementation, its strengths and weaknesses, and issues of outsorcing and sub-outsourcing, the use of benchmarking as a tool to assist management and search for competitive differential. It is also object of study the sinergy that this culture is to the adaptation of new proposals for improvement in processes, such as encouragement to groups of continuous improvement, that using the reference measurement results aligned to corporate proposals, generating gains of scale, greater quality, agility and enables a focus on core business, contributing to the administration of excellence and therefore the creation of value for this organization